Athletic trainers` perspectives on sport psychology: Professional roles, training, and referrals - Ramaeker, J.; Petrie, T. A. (The Sport Psychologist, 2015)
We explored athletic trainers` (ATs) beliefs regarding the roles of fellow ATs and sport psychologists (SPs) when working with athletes, and assessed where ATs` typically refer athletes with psychological concerns. ATs` beliefs and referral preferences across three hypothetical sport performance scenarios also were evaluated. ATs viewed aiding athletes` psychological recovery from injury as their most acceptable role followed by teaching mental skills and counseling regarding personal issues. ATs rated SPs` roles similarly. Regarding the scenarios, ATs were most likely to refer to a SP when performance was affected by mental factors. Considering performance difficulties attributed to interpersonal concerns, ATs were most likely to refer to a counselor. When recovering from physical injury, ATs viewed referring to a sport psychologist and assisting on their own as equally viable options. ATs` views regarding their roles and referral preferences likely reflect educational and clinical experiences. Collaboration between athletic training and sport psychology professional organizations and individual professionals is warranted to enhance athlete care.